Myocardial electrical activity according to daily ECG monitoring in patients with heart failure with preserved ejection fraction and asymptomatic diastolic dysfunction - V. D. Syvolap; Ya. V. Zemlyaniy; E. V. Nazarenko (Zaporožskij Medicinskij Žurnal)
Aim. To evaluate changes in the electrical activity of the myocardium according to the daily monitoring of ECG and explore their relationship with structural and functional condition of the heart in patients with heart failure with preserved ejection fraction and asymptomatic diastolic dysfunction after myocardial infarction on the background of hypertension.